Double negatives in New Testament Greek texts and their translations in the Dangme Bible - Kuwornu-Adjaottor, Jonathan E. T. (HTS teologiese studies, 2025)
The Greek negatives, µὴ and οὐk (which also appear as οὐ, and οὐx depending on the type of beginning alphabet of the word that it precedes), are variedly used in the Greek New Testament and at various instances. With all the relevance of the use of these negatives in New Testament Studies, of special attention is the appearance of the double negative as the combination of οὐ μὴ. Although the double negatives are not translated to stand on their own, their combination in English denotes not at all, in no wise or by no means. Further, this combination has both exegetical and theological significance and implications. This article, therefore, opines that as the double negative places stronger emphasis and vehement force or augments negation or prohibition, it must reflect in the Dangme Bible, Ngmami Klͻuklͻu ͻ (Holy writing), because the force is somehow silent in some of the texts used in the Greek text. It is, therefore, appropriate for biblical exegetes as well as translators to provide the needed attention to this in their attempts to bring the text alive to contemporary audience readers, practitioners and students of the biblical texts. Contribution: This article, therefore, attempted to analyse the translation of the double negative combination in Dangme Bible, Ngmami Klͻuklͻu ͻ reflecting on the implications of its usage.